An analysis of theoretical and empirical relationships between two asphalt binder cracking parameters. (1st June 2021) - Hajj, Ramez; Young, Scott
Abstract : Since the adoption of the Performance Grading criteria, researchers and agencies have dedicated efforts toward supplementing the existing parameters with better indicators of asphalt binder cracking susceptibility. This study seeks to evaluate the relationship between Δ T c and the Glover-Rowe parameter, two such parameters. This study contains three parts: (i) a fundamental examination of the relationship between the indicators, (ii) an empirical study of theseparameters based on an array of data from the existing literature, and (iii) an examination of the basic principles underlying the mechanisms of ductility and nonlinearity in polymer-modified asphalt related to these parameters. The results indicate that the parameters are not fundamentally related, but have some relationship to cracking, reinforcing the importance of considering time and temperature. Additionally, the parameters do diverge in their relationship. Finally, fundamental properties of polymer-modified asphalts reveal the need for considering nonlinear and damaged binder behaviour, and reexamining binder ductility's importance.